The association between organophosphate insecticides, blood pressure dysregulation, and metabolic syndrome among U.S. Adults: NHANES 2015-2016 - Frank Glover; Kyle Steenland; Michael L. Eisenberg; Federico Belladelli; Evan Mulloy; Francesco Del Giudice; William M. Caudle (Hygiene and Environmental Health Advances, 2022)
Organophosphate (OP) insecticides represent some of the most common environmental contaminants in the United States. Organophosphate insecticide use has been associated with numerous adverse health outcomes, including hypertension (HTN) and metabolic syndrome (MetS), but results from current studies are conflicting and inconclusive. In a study of 916 U.S. adults from the 2015–2016 NHANES cycle, we investigated the association between five dialkyl phosphate (DAP) metabolites of OP insecticides and blood pressure parameters (systolic blood pressure, diastolic blood pressure, pulse pressure, mean arterial pressure, HTN), as well the association between total body burden of DAPs with HTN and MetS. Weighted, multivariable linear regression revealed significant, inverse associations between diethylphosphate and systolic blood pressure (β= -0.16 p = 0.02), diethylthiophosphate and systolic blood pressure (β= -0.91 p = 0.01), total DAP exposure and systolic blood pressure (β= -0.13, p = 0.04), and between dimethylphosphate and diastolic blood pressure (β= -0.15, p = 0.0075). No significant associations were observed between total DAP exposure and odds of HTN. We additionally modeled the odds of abnormally high pulse pressure given specific quartile of total DAP exposure. Results showed a significant association between diethylphosphate and odds of abnormal pulse pressure (OR=1.29, 95% CI[1.01,1.65]), and between total DAP exposure and odds of abnormal pulse pressure (OR=1.05, 95% CI[1.03,1.10]). Lastly, we found that adults in the 3rd quartile of OP metabolite exposure had a 3.61 increased odds of having MetS when compared to individuals in the 1st quartile (OR=3.61, 95% CI[1.32,9.85]).Our preliminary findings support data from previous studies suggesting a role for OP insecticides in the pathogenesis of blood pressure dysregulation and MetS. Future studies are warranted to corroborate these findings, determine population-level clinical significance, and to elucidate potential mechanisms explaining these associations.